QARAQALPAQ HÁM ÓZBEK TILLERINDEGI FITONIMLERDIŃ LEKSIKALIQ-SEMANTIKALIQ ANALIZI - Dauletbaeva, N.B. (SCIENCE and SOCIETY, 2025)
This article analyzes the lexical and semantic features of phytonyms in the Karakalpak and Uzbek languages. The origin of phytonyms, their semantic groups, and the commonalities and differences between the two languages were studied on the basis of a comparative analysis. Cultural, historical, and etymological aspects of phytonyms are also considered. The research results serve to determine the principles of formation of phytonyms and to draw important conclusions in the lexicology of Turkic languages.